What One Municipality Has Accomplished: The City of Saco and Its Energy Committee - Peaslee, Travis (Maine Policy Review, 2008)
Travis Peaslee describes the comprehensive efforts of the city of Saco, Maine to reduce energy consumption, increase efficiency, and use new energy sources.